Generalized List Colouring of Graphs - Cho, Eun Kyung; Choi, Ilkyoo; Jiang, Yiting; Kim, Ringi; Park, Boram; Yan, Jiayan; Zhu, Xuding (Graphs and Combinatorics, 2021)
This paper disproves a conjecture in Wang et al. (Graphs Comb. 31:1779–1787, 2015) and answers in the negative a question in Dvořák et al. (Electron J Comb:P26, 2019). In return, we pose five open problems.
Keywords: Choice number; Generalized list colouring; List star arboricity; List vertex arboricity